THE RETURN TO NATIONAL EDUCATIONAL TRADITIONS IN MODERN RUSSIAN PEDAGOGY: CONTINUITY AND THE SYNTHESIS OF IMPERIAL AND SOVIET HERITAGE - Oganyan T. B.; Martynenko E. V. (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
This article examines the current shift in Russian pedagogical science towards national educational traditions, emphasizing pedagogical continuity. Framed by the analysis of Presidential Decree No. 809 (2022), the study explores the synthesis of pre-revolutionary and Soviet educational approaches. The article identifies educational traditions relevant for contemporary practice and substantiates their importance for forming civic identity and ensuring the spiritual security of society. The research concludes that modern Russian pedagogy is creatively integrating these traditions to address current challenges while maintaining continuity with the best domestic practices.